Inhibition of the Photosynthetic Capacity of Isolated Chloroplasts by Ozone - Coulson, Christopher (1974)
Isolated spinach chloroplasts have been used as a model system for studying the interaction of ozone, a component of photochemical smog, with plant membranes. Ozone bubbled into a suspension of isolated chloroplasts inhibits electron transport in both photosystems without uncoupling ATP production. Photosystem I (reduced 2,6-dichlorophenolindolphenol → NADP(+)) is a little more sensitive than photosystem II (H(2)O → 2,6-dichlophenolindolphenol). Ozone does not act as an energy transfer inhibitor, since the drop in ATP production and high energy intermediate (measured by amine-induced swelling) is nearly parallel to the decline in electron transport. A reasonable hypothesis is that ozone disrupts the normal pathway of energy flow from light-excited chlorophyll into the photoacts by a disruption of the components of the membrane but not a general disintegration of the membrane. In addition, ozone does not seem to penetrate into the grana region through the outer membrane of intact plastids, since ozone lowers the bicarbonate-supported O(2) evolution but does not affect the rate of ferricyanide reduction in the same plastids after osmotic disruption. This would indicate that the effect of ozone on green plants, at low concentrations, may be due to the interaction of ozone with the first membrane it contacts and not directly with internal metabolic processes.